Association between family income to poverty ratio and severe headache/migraine in the American adults: data from NHANES 1999–2004 - Sun, Lingling; Zhao, Rongjian; You, Xuemei; Meng, Junpeng; Meng, Lin; Di, Haili (Frontiers in Neurology, 2024)
BackgroundThe relationship between family income to poverty ratio (PIR) and severe headache/migraine remains unclear.MethodsData for this cross-sectional study were obtained from NHANES 1999–2004. PIR was the exposure variable, and severe headache/migraine was the dependent variable. We performed univariate analyses of severe headache/migraine, PIR, and other covariates. The association between PIR and severe headache/migraine was tested using multiple regression models. Furthermore, interaction tests and stratified analyses assessed the relationship between PIR and severe headache/migraine across subgroups.ResultsThere were a total of 8,800 participants: 4,833 (54.92%) males and 3,967 (45.08%) females, 1,714 (19.48%) with severe headache/migraine and 7,086 (80.52%) without severe headache/migraine. After adjustment for all variables, PIR negatively correlated with severe headache/migraine OR = 0.86 95% CI (0.83, 0.90) p < 0.0001. The variable PIR was categorized as the low-income (PIR < 1), the middle-income (PIR1-4), and the high-income (PIR > 4). Notably, there was a significant difference in trend for the high-income group (PIR > 4) compared to the control low-income group (PIR < 1) (all P for interaction<0.05). Dose–response correlations were also analyzed using smoothed curve fitting, revealing a negative correlation between PIR and severe headache/migraine (p < 0.0001). Subgroup analysis results indicated that the negative association between PIR and severe headache/migraine was more pronounced in the following populations: males (OR = 0.84 95% CI (0.79, 0.90), <60 years old [Age < 45 group OR = 0.81 95% CI (0.76, 0.85)], Age 45–60 group OR = 0.86 95% CI (0.79, 0.93), and those with education levels ≥high school [High School OR = 0.87 95% CI (0.81, 0.95), >High School OR = 0.82 95% CI (0.78, 0.87)].ConclusionThere is a negative correlation between PIR and the incidence of severe headaches/ migraine in Americans aged 20 years or older. This study has implications for the comprehensive management of patients with severe headache/migraine.